Les figures de construction dans les textes persuasifs d’après l’exemple des annonces matrimoniales - Otulak-Komenda, Monika (Studia Romanica Posnaniensia, 2010)
A sender of a personal ad, who usually does not have any theoretical knowledge of rhetoric, intuitively uses simple schemes in the text which are based on the syntactic modifications of zero level. The schemes, which are discussed in this article, do not introduce any changes on the semantic level, as a result, they do not cause ambiguity and they do not make the text’s reception more difficult. On the one hand, making such schemes is easy, by and large, it does not demand the knowledge of theoretical basis of rhetoric. On the other hand, the schemes have an influence on rhythmicality and dynamic of the text. Consequently, they make the reception of the text easier and, in addition, the text becomes more attractive for a virtual recipient.